The frequency characteristic Of MEMS beam resonator - Bibikov, Тaras; Bogdan, Oleksandr; Petrishev, Oleg; Yakymenko, Yuriy; Bogdan, Tetiana (Видавництво Львівської політехніки, 2010)
In this paper the model of the MEMS (microelectromechanical systems) beam resonator.
Keywords: MEMS; resonator; frequency Characteristic